The role of capital adequacy standards in creating financial safety of the bank: the evaluation and analysis of the survey results - Pyka, Irena; Nocoń, Aleksandra; Muszyński, Mateusz (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: After the global financial crisis, banks’ financial safety has been considered as a public good and put under closer control and supervision. The prudential regulations of credit institutions which are the main subject of the study, have been significantly tightened. Although the minimum level of banks’ own funds, set adequately to the risk, had been a fundamental indicator of banks’ financial safety since the end of 1980s, after the global financial crisis the quality of this capital has changed and the scope of its regulation has been increased. By respecting the new prudential standards of the Basel Committee on Banking Supervision at the international level, financial safety of the banks has been additionally put under the macro-supervision. The concern about the overregulation of the banking system raises many controversies, what justifies conducting research on this subject. Aim: The main purpose of the article is to identify changes in the bank’s strategies of creating financial safety after the global financial crisis, considering macro- and micro-prudential regulations, aimed at strengthening the level and quality of bank capital, based on the results of the conducted research. Results: The results of the empirical research indicate that there is a strong belief among management staff in commercial banks in Poland that the increase in the level and structure of the own funds in credit institutions rises their financial safety. The results confirm the intensification of the process of implementing Basel regulations in commercial banks in Poland.